Identification of EMT-Related Gene Signatures to Predict the Prognosis of Patients With Endometrial Cancer - Cai, Luya; Hu, Chuan; Yu, Shanshan; Liu, Lixiao; Zhao, Jinduo; Zhao, Ye; Lin, Fan; Du, Xuedan; Yu, Qiongjie; Xiao, Qinqin (Frontiers in Genetics, 2020)
Background: Endometrial cancer (EC) is one of the most common gynaecological cancers. Epithelial-mesenchymal transition (EMT) is believed to be significantly associated with the malignant progression of tumours. However, there is no relevant study on the relationship between EMT-related gene (ERG) signatures and the prognosis of EC patients. Methods: We extracted the mRNA expression profiles of 543 tumour and 23 normal tissues from The Cancer Genome Atlas (TCGA) database. Then, we selected differentially expressed ERGs (DEERGs) among these mRNAs. Next, univariate and multivariate Cox regression analyses were performed to select the ERGs with predictive ability for the prognosis of EC patients. Additionally, risk score models were constructed based on the selected genes to predict patients’ overall survival (OS), progression-free survival (PFS) and disease-free survival (DFS). Finally, nomograms were constructed to estimate the OS and PFS of EC patients, and pan-cancer analysis was performed to further analyse the functions of a certain gene. Results: Twelve OS-, twelve PFS- and six DFS-related ERGs were obtained. By constructing the prognostic risk score model, we found that the OS, PFS and DFS of the high-risk group were notably poorer. Last, we found that AQP5 appeared in all three gene signatures, and through pan-cancer analysis, it was also found to play an important role in immunity in Lower Grade Glioma (LGG), which may contribute to the poor prognosis of LGG patients. Conclusions: We constructed ERG signatures to predict the prognosis of EC patients using bioinformatics methods. Our findings provide a thorough understanding of the effect of EMT in patients with EC and provide new targets and ideas for individualized treatment, which has important clinical significance.